1997
DOI: 10.1177/1045389x9700800704
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Feedback Control of Magnetically-Activated Gels

Abstract: Polymer gels that exhibit a change in volume in response to a small change in an environmental parameter such as temperature have been fabricated and studied for several decades. We have developed gels that change volume in response to an applied alternating magnetic field. These gels could serve as actuators in servomechanisms. This paper presents practical techniques for using closed-loop feedback to control the position of magnetically-triggered polymer gels. Experimental results are presented that demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The stated objective of this research is the development of a muscle-and tendon-like actuator. While some investigators have proposed the use of commercially available actuators (e.g., Yoda and Shiota 1994;Cocatre-Zilgien, Delcomyn and Hart 1996;Wu, Hwang and Chang 1997), others have suggested novel actuators such as shape-memory alloys (Mills 1993), electro-reactive gels (Mitwalli et al 1997), ionic polymer-metal composites (Mojarrad and Shahinpoor 1997), and stepper motors with ball screw drives connected to elastic Strain − percent Stress − MPa Bobbert & Ingen Schenau 1990Zajac 1989Voigt et al 1995EST Model Bobbert et al 1986Hof 1998 Fig. 4.…”
Section: Artificial Muscle and Tendonmentioning
confidence: 99%
“…The stated objective of this research is the development of a muscle-and tendon-like actuator. While some investigators have proposed the use of commercially available actuators (e.g., Yoda and Shiota 1994;Cocatre-Zilgien, Delcomyn and Hart 1996;Wu, Hwang and Chang 1997), others have suggested novel actuators such as shape-memory alloys (Mills 1993), electro-reactive gels (Mitwalli et al 1997), ionic polymer-metal composites (Mojarrad and Shahinpoor 1997), and stepper motors with ball screw drives connected to elastic Strain − percent Stress − MPa Bobbert & Ingen Schenau 1990Zajac 1989Voigt et al 1995EST Model Bobbert et al 1986Hof 1998 Fig. 4.…”
Section: Artificial Muscle and Tendonmentioning
confidence: 99%
“…By inductive heating in an alternating magnetic field, the shapememory effect of the composites can be triggered. Prior studies reported inductive heating of smart hydrogels (19), ferrogels (20,21), and ferrofluids (22,23) in alternating magnetic fields by using embedded magnetic particles (21)(22)(23)(24)(25)(26)(27). The mechanisms of heat generation are hysteresis loss and͞or related processes that are direct result of superparamagnetism (23).…”
mentioning
confidence: 99%
“…Triggers other than solvent composition, such as temperature, light (14), and magnetic field (15), can, in principle, be used by properly designing the gel composition.…”
Section: Discussionmentioning
confidence: 99%